Comparison of Some Methods for Estimating the Scheff’e Model of the Mixture - مهدي دجلة ابراهيم; فرحان حلا سلمان (Journal of Economics and Administrative Sciences, 2019)
Because of the experience of the mixture problem of high correlation and the existence of linear MultiCollinearity between the explanatory variables, because of the constraint of the unit and the interactions between them in the model, which increases the existence of links between the explanatory variables and this is illustrated by the variance inflation vector (VIF), L-Pseudo component to reduce the bond between the components of the mixture. To estimate the parameters of the mixture model, we used in our research the use of methods that increase bias and reduce variance, such as the Ridge Regression Method and the Least Absolute Shrinkage and Selection Operator (LASSO) method as well as the Elastic Net estimation method, In R the comparison criterion is the absolute mean percent error (MAPE).